SINTESIS PLASTIK BIODEGRADABLE DARI PATI GANYONG DENGAN MODIFIKASI KASEIN SUSU AFKIR DAN PLASTICIZER SORBITOL - Sriyana, Herman Yoseph; Prastyawati, Soraya (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
Canna starch has the potential to be a raw material for biodegradable plastic because it has a total starch content of 93.30%, amylose content of 42.40% and amylopectin 50.90%. The research aims to study the effect of the ratio of canna starch and casein rejected milk with sorbitol modification on the characteristics of biodegradable plastic. The variables of this research were the ratio of canna starch and casein from rejected milk (4:0; 3:1; 2:2) and stirring for 30 minutes at 75Â°C and the addition of sorbitol (2%, 3%, 4% , 5%). The process of making biodegradable plastic is carried out by pouring a biodegradable plastic solution according to variables into a mold, then drying it using an oven at 70Â°C for 6 hours and the mold is taken out to dry at room temperature for 24 hours. The plastic formed is tested for tensile strength, elongation, biodegradation, morphology. The results of this research show that the higher the canna starch added and the lower the casein added, the more water resistance, tensile strength, elongation increases, and biodegradation increases. The smaller the ratio of canna starch and milk casein (the greater the amount of milk casein), the higher the water resistance, tensile strength, elongation and biodegradability of the resulting bioplastic. The best combination ratio of starch and casein was obtained at a ratio of 4:0 which provided the highest water resistance of 81.82%, the highest tensile strength of 5.48 MPa, the highest elongation of 26.67, and the highest biodegradation of 0.08. The higher the amount of sorbitol added increases the value of elongation, biodegradation. The best addition of sorbitol was obtained at a concentration of 5% which provided the highest elongation of 8.57, biodegradation of 0.11, while the best tensile strength was obtained at a concentration of 1% of 3.40 MPa.